Rapid self-healing hydrogels - Phadke, Ameya; Zhang, Chao; Arman, Bedri; Hsu, Cheng-Chih; Mashelkar, Raghunath Anant; Lele, Ashish K.; Tauber, Michael J.; Arya, Gaurav; Varghese, Shyni (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Synthetic materials that are capable of autonomous healing upon damage are being developed at a rapid pace because of their many potential applications. Despite these advancements, achieving self-healing in permanently cross-linked hydrogels has remained elusive because of the presence of water and irreversible cross-links. Here, we demonstrate that permanently cross-linked hydrogels can be engineered to exhibit self-healing in an aqueous environment. We achieve this feature by arming the hydrogel network with flexible-pendant side chains carrying an optimal balance of hydrophilic and hydrophobic moieties that allows the side chains to mediate hydrogen bonds across the hydrogel interfaces with minimal steric hindrance and hydrophobic collapse. The self-healing reported here is rapid, occurring within seconds of the insertion of a crack into the hydrogel or juxtaposition of two separate hydrogel pieces. The healing is reversible and can be switched on and off via changes in pH, allowing external control over the healing process. Moreover, the hydrogels can sustain multiple cycles of healing and separation without compromising their mechanical properties and healing kinetics. Beyond revealing how secondary interactions could be harnessed to introduce new functions to chemically crosslinked polymeric systems, we also demonstrate various potential applications of such easy-to-synthesize, smart, self-healing hydrogels.
Keywords: adhesives; biomimetic materials; Hydrophobicity; molecular dynamics; smart materials

Reporter nanoparticle that monitors its anticancer efficacy in real time - Kulkarni, Ashish; Rao, Poornima; Natarajan, Siva; Goldman, Aaron; Sabbisetti, Venkata S.; Khater, Yashika; Korimerla, Navya; Chandrasekar, Vineethkrishna; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The ability to monitor the efficacy of an anticancer treatment in real time can have a critical effect on the outcome. Currently, clinical readouts of efficacy rely on indirect or anatomic measurements, which occur over prolonged time scales postchemotherapy or postimmunotherapy and may not be concordant with the actual effect. Here we describe the biology-inspired engineering of a simple 2-in-1 reporter nanoparticle that not only delivers a cytotoxic or an immunotherapy payload to the tumor but also reports back on the efficacy in real time. The reporter nanoparticles are engineered from a novel two-staged stimuli-responsive polymeric material with an optimal ratio of an enzyme-cleavable drug or immunotherapy (effector elements) and a drug function-activatable reporter element. The spatiotemporally constrained delivery of the effector and the reporter elements in a single nanoparticle produces maximum signal enhancement due to the availability of the reporter element in the same cell as the drug, thereby effectively capturing the temporal apoptosis process. Using chemotherapy-sensitive and chemotherapy-resistant tumors in vivo, we show that the reporter nanoparticles can provide a real-time noninvasive readout of tumor response to chemotherapy. The reporter nanoparticle can also monitor the efficacy of immune checkpoint inhibition in melanoma. The self-reporting capability, for the first time to our knowledge, captures an anticancer nanoparticle in action in vivo.
Keywords: chemotherapy; immunotherapy; monitoring; nanoparticle; reporter